Advanced nanomaterials and nanocomposites for bioelectrochemical systems (Micro & nano technologies., 2023)
Advanced Nanomaterials and Nanocomposites for Bioelectrochemical Systems covers advancements in nanomaterial and nanocomposite applications for microbial fuel cells. One of the advantages of using microbial fuel cells is the simultaneous treatment of wastewater and the generation of electricity from complex organic waste and biomass, which demonstrates that microbial fuel cells are an active area of frontier research. The addition of microorganisms is essential to enhance the reaction kinetics. This type of fuel cell helps to convert complex organic waste into useful energy through the metabolic activity of microorganisms, thereby generating energy. By incorporating nano-scale fillers into the nanocomposite matrix, the performance of the anode material can be improved. This is an important reference source for materials scientists and engineers who want to learn more about how nanotechnology is being used to create more efficient fuel cells. Describes the major nanomaterials and nanocomposites used in microbial fuel cells Explains how microbial fuel cells are being used in renewable energy applications Assesses the challenges of manufacturing nanomaterials for microbial fuel cells on an industrial scale.